The brief overview, antivirus and anti-SARS-CoV-2 activity, quantitative methods, and pharmacokinetics of cepharanthine: a potential small-molecule drug against COVID-19 - Xia, Binbin; Zheng, Li; Li, Yali; Sun, Wenfang; Liu, Yang; Li, Liushui; Pang, Jingyao; Chen, Jing; Li, Jiaxin; Cheng, Hua (Frontiers in Pharmacology, 2023)
To effectively respond to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an increasing number of researchers are focusing on the antiviral activity of cepharanthine (CEP), which is a clinically approved drug being used for over 70 years. This review aims to provide a brief overview of CEP and summarize its recent findings in quantitative analysis, pharmacokinetics, therapeutic potential, and mechanism in antiviral and anti-SARS-CoV-2 activity. Given its remarkable capacity against SARS-CoV-2 infection in vitro and in vivo, with its primary target organ being the lungs, and its good pharmacokinetic profile; mature and stable manufacturing technique; and its advantages of safety, effectiveness, and accessibility, CEP has become a promising drug candidate for treating COVID-19 despite being an old drug.